Chan, Anita, Children of Mao. Personality Development and PoliticalActivism in the Red Guards Generation, Seattle, University of Washington Press, 1985, VIII + 254 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1986)
-